0745 Sleep-Related Hypoxemia Association with Incident Atrial Fibrillation in a Clinic-Based Cohort. (25th May 2022) - Heinzinger, Catherine; Thompson, Nicolas; Milinovich, Alex; Foldvary-Schaefer, Nancy; Van Wagoner, David; Chung, Mina; Mehra, Reena
Abstract: Introduction: Sleep disordered breathing (SDB) has been implicated in atrial fibrillation (AF) in population-based studies, however, its role remains unclear and inconsistent. We hypothesize greater risk of 5-year incident AF with SDB and sleep-related hypoxia in a clinic-based cohort. Methods: Cleveland Clinic patients (age>18) who underwent polysomnogram (PSG) or split studies 11/27/2004-12/30/2015 with >3 hours diagnostic time were examined. Predictors include AHI, % sleep time oxygen saturation<90% (T90), and minimum and mean oxygen saturation(minSaO2 and meanSaO2, respectively). Cox proportional hazard models were fit with time from sleep study to AF diagnosis as the dependent variable. Covariates included age, sex, race, body mass index(BMI), cardiovascular risk factors (hypertension, diabetes mellitus, hyperlipidemia), heart failure, coronary artery disease, myocardial infarction, history of coronary artery bypass grafting, chronic obstructive pulmonary disease, tobacco use, and use of anti-arrhythmic drugs. Data were censored at date of last follow up or at 5-years. Results: The sample was comprised of 43, 634 patients: age 51.7±14.5, 51.9% male, 74.5% White, and 7.1%(n=3, 090) with AF. Of those without AF, 1, 176(2.9%) developed 5-year incident AF. For each 10% increase in T90, incident AF increased by 7% (HR=1.07, 95%CI=1.05-1.10). Compared to reference, patients with 25.01-50%, 50.01-75%, and 75.01-100% time T90 had 22% (HR=1.22, 95%CI=1.01-1.46), 49% (HR=1.49, 95%CI=1.20-1.85), and 65% (HR=1.65, 95%CI=1.26-2.15) higher incident AF, respectively. For every 10-unit increase in minSaO2 and meanSaO2, incident AF decreased by 11%(HR=0.89, 95%CI=0.83-0.95) and 23% (HR=0.77, 95%CI=0.68-0.86), respectively. AHI did not demonstrate a statistically significant relationship with incident AF at a significance level of 0.05. Conclusion: Sleep-related hypoxemia, defined by cumulative burden below 90% SaO2, demonstrated an association with incident AF in this large clinic-based cohort, even considering confounding factors. On the other hand, SDB severity as defined by AHI did not demonstrate this relationship. These findings are consistent with experimental models that identify intermittent hypoxia and oxidative stress leading to alterations of the cardiac substrate, thus implicating sleep-related hypoxemic mechanisms as a salient driver in the evolution of atrial arrhythmogenesis. Support (If Any): Cleveland Clinic Neurological Institute Center for Outcomes Research & Education Pilot Grant, Neuroscience Transformative Research Resource Development Award